The Correlation between Blood Glucose Levels, Body Mass Index (BMI), and Age on Prolanis Patients in Baturraden Public Health Care Center II - Sri Yuliati; Retno Sulistiyowati; Umi Solikhah; Kurnia Ritma Dhanti (Institute of Computer Science (IOCS), 2022)
Health services through the chronic disease management program or Prolanis is a process to determine the health condition of patients with chronic diseases regularly, glucose being one of the parameters of the examination. Glucose levels are influenced by several factors, which are age and body mass index. This study aims to determine the relationship between blood glucose levels with body mass index and age in prolanis patients at Baturraden II Health Center. This type of research is a quantitative study with a cross sectional design using a total sampling technique and the GOD-PAP (Glucose Oxidase Para Amino Peroxidase) examination method on prolanis patients at Baturraden II Health Center. The research was carried out in April 2022 and obtained the results of the examination of blood glucose levels with an average of 133.30 mg/dl, the relationship between age and body mass index respectively to blood glucose levels was p value = 0.701 and p value = 0.211. So it can be concluded that there is no significant relationship between blood glucose levels with body mass index and age in prolanis patients at Baturraden II Health Center.